2016
DOI: 10.1161/jaha.116.003337
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Time Physical Activity and Cardio‐Metabolic Health: Results From the Brazilian Longitudinal Study of Adult Health (ELSA‐Brasil)

Abstract: BackgroundAlthough increasing effort has been devoted to the promotion of a healthy lifestyle such as leisure time physical activity for cardio‐metabolic health, specific evidence supporting health policy remains sparse, particularly in those ethnically diverse populations where cardio‐metabolic diseases are reaching epidemic proportion and yet are grossly understudied.Methods and ResultsWe conducted a cross‐sectional analysis of the baseline data from 10 585 participants aged 35 to 74 free of cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 42 publications
0
22
0
10
Order By: Relevance
“…516 Recently, our research group published results on the baseline data (first wave) of the ELSA-Brasil showing inverse associations between leisure-time physical activity alone and hypertension, diabetes, and 10-year cardiovascular disease risk, both for men and women. 17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…516 Recently, our research group published results on the baseline data (first wave) of the ELSA-Brasil showing inverse associations between leisure-time physical activity alone and hypertension, diabetes, and 10-year cardiovascular disease risk, both for men and women. 17…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, various studies have shown that physical activity, particularly when performed within the domain of leisure time, is inversely associated with cardiometabolic diseases including diabetes, dyslipidemias, hypertension, and inflammatory markers. 1217…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been shown to be inversely associated with blood pressure levels, diabetes, lipid alterations, and other cardiovascular events. 4,8 With respect to duration and intensity of physical activity required for these benefits to occur, a recent publication suggested that 180 to 300 minutes of moderate to intense activity weekly for men and 150 to 300 minutes of moderate to intense activity for women would be the most adequate measure for promoting cardiovascular and metabolic health benefits. 9 These recommendations are in agreement with the main physical activity guidelines published by international organizations.…”
Section: Physical Activity and Cardiovascular And Metabolic Healthmentioning
confidence: 99%
“…LTPA is commonly associated with a variety of health related benefits such as improved cardiovascular (Fransson et al 2003;Lin et al 2016) and mental health (Stathi et al 2002), and reduced stress (Benson 1975;Iwasaki 2006) and obesity (Bauman et al 2008) levels. In addition to these physical health benefits, engaging in physical activity during leisure draws people together socially and encourages the development of durable social networks (Glover and Parry 2008;Saito et al 2013;Coleman and Iso-Ahola 1993).…”
Section: Introductionmentioning
confidence: 99%